2016
DOI: 10.3343/alm.2016.36.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Impact of Heterogeneous Vancomycin-Intermediate Staphylococcus aureus Isolated From Hospitalized Patients

Abstract: BackgroundWe estimated the prevalence and clinical impact of heterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA). The concordance between macromethod and glycopeptide resistance detection (GRD) E tests was determined. In addition, predictors of clinical outcomes in hospitalized patients with S. aureus bacteremia (SAB) or pneumonia (SAP) were evaluated.MethodsWe obtained 229 consecutive S. aureus isolates from all hospitalized patients at two university hospitals located in Busan and Yangsan, Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…As regards vancomycin susceptibility, hVISA was first reported in Japan in 1997 and along with VISA has since been identified worldwide from many countries including the United States, Japan, Australia, France, Scotland, Brazil, South Korea, Hong Kong, South Africa, Thailand, Israel, and others. [3,4] In India, Menezes et al [15] in 2008 reported the emergence of vancomycin-intermediate Staphylococcus species in Southern India using the revised guidelines. Of 102 oxacillin-resistant S. aureus isolates, one was found to be a VISA strain (MIC 5 µg/ml).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As regards vancomycin susceptibility, hVISA was first reported in Japan in 1997 and along with VISA has since been identified worldwide from many countries including the United States, Japan, Australia, France, Scotland, Brazil, South Korea, Hong Kong, South Africa, Thailand, Israel, and others. [3,4] In India, Menezes et al [15] in 2008 reported the emergence of vancomycin-intermediate Staphylococcus species in Southern India using the revised guidelines. Of 102 oxacillin-resistant S. aureus isolates, one was found to be a VISA strain (MIC 5 µg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] For MRSA and multidrug-resistant (MDR) S. aureus infections, vancomycin is considered the mainstay of antimicrobial therapy and has been the treatment of choice for serious MRSA infections since 1958. [3] However, emerging reports of vancomycin minimum inhibitory concentrations (MIC) creep, reduced vancomycin susceptibility (RVS), and even vancomycin resistance in clinical MRSA isolates from different geographical regions are disturbing, because of minimal alternative therapeutic options. [3][4][5][6] This is because the clinical effectiveness of vancomycin may be compromised even against vancomycin-sensitive S. aureus (VSSA) strains whose MICs are within the Clinical and Laboratory Standards Institute (CLSI) susceptible range (≤2 µg/ml).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Studies that followed, confirmed the high specificity of E test GRD ranging from 85.8% to 97% but lower sensitivity levels ranging from 57% to 82%. 15,16 Presently, most of the studies recommend using two different methods for more accurate detection of VISA/hVISA strains (CDC).…”
Section: Discussionmentioning
confidence: 99%